A psychological intervention reduces doping likelihood in British and Greek athletes: A cluster randomized controlled trial. (July 2022) - Kavussanu, Maria; Barkoukis, Vassilis; Hurst, Philip; Yukhymenko-Lescroart, Mariya; Skoufa, Lida; Chirico, Andrea; Lucidi, Fabio; Ring, Christopher
Abstract: Background: Current attempts to prevent doping through deterrence and education have had limited success and have been constrained to one country. Targeting psychological variables that have been empirically associated with doping likelihood, intention, or behaviour may help in developing interventions that are effective in preventing doping in sport. Objectives: Guided by social cognitive theory and empirical research, the main purpose of this research was to develop an anti-doping intervention that targets three psychological variables (i.e., anticipated guilt, moral disengagement, and self-regulatory efficacy) and determine whether it is more effective than an educational intervention in reducing doping likelihood in British and Greek athletes. Method: Eligible participants were identified via a screening survey administered to 934 athletes in the United Kingdom and Greece. A total of 19 sport clubs (208 athletes) across the two countries were randomly assigned to either the psychological or the educational intervention. Each intervention consisted of six 1-h sessions delivered to small groups of athletes over 6–8 weeks. Athletes completed measures of doping likelihood, anticipated guilt, moral disengagement, and self-regulatory efficacy pre and postintervention and at a 2-month follow-up. Results: A multilevel piecewise growth model was used to examine changes in study outcomes. Analysis showed that the psychological intervention was more effective than the educational intervention in reducing doping likelihood from pre to post, but the effects of the two interventions were similar at follow-up. These effects were not affected by country. Both interventions reduced moral disengagement from pre to post, and these effects were maintained at follow-up. The psychological intervention was also more effective than the educational intervention in increasing anticipated guilt from pre to follow-up. Conclusions: Targeting psychological variables in anti-doping interventions should aid our efforts to prevent doping in sport. Highlights: A theory-driven and evidence-based psychological intervention was developed and evaluated in British and Greek athletes. The psychological intervention was more effective than the educational intervention in reducing doping likelihood from pre to post. Both interventions reduced moral disengagement from pre to post and these effects were maintained at follow-up. The psychological intervention was more effective than the educational intervention in increasing anticipated guilt from pre to follow-up.